Sectoral Potential Analysis For Development Planning In Binjai, Deli Serdang, Karo (Bidangro) Metropolitan Area - Lubis, Maksum Syahri; Putra, Ilham Mirzaya (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
The economic potential is the ability of the local economy that is feasible and can be developed so that it becomes a source of livelihood for the community in the local area Thus, it is necessary to know the superior sectors owned by the region so that their potential can be increased and can effectively support economic development. This study aims to determine the potential sector; progressive, has a comparative advantage, and stands out to be developed in Binjai, Deli Serdang, and Karo Regency. The data collection method is non-participant observation based on secondary data published by Badan Pusat Statistik. The analytical tools used in this research are Location Quotient (LQ), Shift and Share, Growth Ratio Model, and Overlay. The results of this study were: 1) Provision of electricity and gas sector are the potential sector in Binjai, Deli Serdang, and Karo Regencies/Cities, 2) In Binjai City there are seven potential sectors. In Karo Regency there are seven potential sectors. Meanwhile in Deli Serdang Regency there are only two potential sectors. 3) in Binjai City and Deli Serdang Regency there are four sectors which has sluggish growth but has a prominent and comparative advantage. Furthermore there are eight sectors in Karo regency. The role of Medan as the main area, is slowly being taken over by the city of Binjai which does not excel in the agricultural or mining sectors. Furthermore, The position of Deli Serdang Regency which is close to two cities is considered very strategic. The limited land area in urban areas has encouraged increased construction activities in Deli Serdang district. Otherwise, Residents of urban and surrounding areas spend a lot of time on vacation and relaxing in Karo regency. This condition encourages many potential sectors in this district.